Fuzzy AHP model for challenges to thermal power plant establishment in India. (10th April 2019) - Mittal, Varinder Kumar; Sindhwani, Rahul; Shekhar, Himanshu; Singh, Punj Lata
Thermal power plant is a huge project in context of resource utilisation, time required for its completion and also large amount of funds are required for its establishment. So, delay in any activity especially activity of critical path would results in delay of whole project. Due to delay, the stress on the resources would also increase, which may further result in substandard quality of work. A fuzzy AHP process model has been used to prioritise the challenges to thermal power plant establishment through the inputs by experts from managers at the actual construction sites, designers, and consultants. The challenges identified in the present study can be categorised in three categories viz. high impact, medium impact and least impact challenges. This paper presented the ranking of 19 challenges faced in the establishment of a new thermal power plant in India.